1997
DOI: 10.1016/s0016-5107(97)70123-8
|View full text |Cite
|
Sign up to set email alerts
|

Lack of complications following short-term stent therapy for extrahepatic bile duct strictures in primary sclerosing cholangitis

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 11 publications
(3 reference statements)
1
29
0
3
Order By: Relevance
“…Development of a DS is a common complication of PSC that can portend a diagnostic challenge as well as significant morbidity and mortality 16, 17, 18. Nevertheless, consensus on the definition of a DS, indications for and means of further evaluation and treatment, and appropriate follow‐up has yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Development of a DS is a common complication of PSC that can portend a diagnostic challenge as well as significant morbidity and mortality 16, 17, 18. Nevertheless, consensus on the definition of a DS, indications for and means of further evaluation and treatment, and appropriate follow‐up has yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the Amsterdam group aimed at inserting a single 10-Fr stent, and if this was not possible at first attempt, it was preceded by 1-week stenting with a 7-Fr stent or insertion of a nasobiliary catheter (55,61). The Mayo group used 7-10-Fr stents at the endoscopist's discretion (53).…”
Section: Stent Therapymentioning
confidence: 99%
“…All studies mentioned focused on clinical and serum liver tests, not radiological data, to assess the shortterm effect of therapeutic ERCP (53,55,61,62). Endoscopic treatment has been repeated in a sizeable proportion of patients: for example, with long median stenting periods (3 months), the median number of repeated ERCPs per patients ranged between 3 and 5 during follow-up periods of 29 and 22 months in two studies (53,62) while following a short stenting period (mean, 11 days) repeat ERCP rates at one and three years after treatment were estimated at 20% and 40%, respectively (55).…”
Section: Duration Of Stentingmentioning
confidence: 99%
“…Endoprostheses can be placed across strictures, but stent occlusion and cholangitis are frequent, and prospective studies failed to show their benefit. [131][132][133][134][135] Endoscopic dilation of dominant strictures is currently widely practiced despite the lack of prospective randomized controlled trials demonstrating its benefit. 136,137 Retrospective analyses using the Mayo Risk Score to model outcome, however, have suggested that endoscopic dilatation of dominant strictures does improve survival.…”
Section: Dr Marshall Kaplan (Tufts-new England Medicalmentioning
confidence: 99%